Interest and Transformative Experience as Predictors of Geoscience Academic and Career Choice - Amanda D. Manzanares; Kevin J. Pugh (Behavioral Sciences, 2025)
Recruitment and retention of students in STEM fields continues to be a challenge. Existing models of recruitment and retention emphasize the role of domain interest and identity. In the current research, we investigated the role of transformative experience combined with domain interest/identity in predicting academic and career choice. Transformative experiences represent a form of deep engagement in which students actively apply school learning in their everyday lives and find value in doing so. We looked specifically at academic and career choice, i.e., available educational paths and various career options, in the field of geoscience, as the geosciences currently struggle to attract and retain majors, resulting in a lack of professionals to fill these jobs. We collected survey data from students (n = 60) at three U.S. universities, and used hierarchical multiple regression to investigate self-efficacy, pre-geoscience interest/identity, transformative experience, and post-geoscience interest/identity as predictors of geoscience academic and career choice. The full regression model explained 69% of the variance in geoscience academic/career choice. Further, stepwise regression analysis revealed that post-geoscience interest/identity fully mediated the relations between the other significant predictors (pre-geoscience interest/identity and transformative experience) and geoscience academic/career choice.